Técnica del discurso y su incidencia en la destreza oral del idioma inglés de los estudiantes de noveno año de EGB de la Unidad Educativa 23 de Junio del Cantón Baba Provincia de Los Ríos - Murillo Cedeño, Melissa Mercedes (2019)
The technique of speech is an oral narration on a specific topic that seeks to persuade the listener and issues a message in a coherent and clear manner. A study about speech techniques is presented below and how they affect the development of oral proficiency in the English language of the ninth-year students of the Unidad Educativa 23 de Junio of the Baba town. For this where used surveys to the authorities, teachers and students in order to get a meaningful learning of the English language. With the development of this research, it was determined that teachers use poor techniques to improve the development of oral English language skill in students; So it can be concluded that it is necessary to apply the Technique of Speech to precisely guide the development of a specific topic in the language where the student can argue feel confident and improve communication. A guide is applied for the application of the technique of speech for the development of oral English language skills.